A DFT study on the hydrogen storage performance of the Sb monolayer decorated with Li, Na or K. (January 2021) - Xi, Ping; Tan, Lun; Yang, Shulin; Xu, Huoxi; Lan, Zhigao; Wang, Zhao; Gu, Haoshuang
Abstract: The adsorption of the hydrogen molecule on the Sb monolayer decorated with one Li, Na or K atom was calculated via the first-principles density functional theory calculations. The Li, Na or K atom could be reasonably distributed and decorated on the surface of the Sb monolayer with a deceasing binding energy of −2.184 eV, −1.692 eV or −1.596 eV, respectively. The introduced hydrogen molecule was found to be stably adsorbed on the built three modified Sb monolayers and tended to interact more strongly with the Li atom with a higher adsorption energy of −0.205 eV. A molecular dynamics simulation also confirmed that the hydrogen molecule could be still adsorbed on the Li-decorated Sb monolayer at 300 K (room temperature). The further study revealed that there would be four hydrogen molecules chemically stored on the surface of the Li-decorated Sb monolayer with the average adsorption energy of −0.133 eV at 300 K. Our study indicated that the Li-decorated Sb monolayer could be an effective substrate to interact with the hydrogen molecule and also be applied to successfully store the hydrogen molecules at room temperature. Highlights: The Li, Na or K atom could be stably decorated on the surface of the Sb monolayer. The H2 interacted more strongly with the Li atom than the Na or K atom. Four H2 could be adsorbed on the Sb monolayer decorated with one Li atom at 300 K. The Li-decorated Sb monolayer is effective to store the hydrogen molecules at RT.